Translational Genetic Modelling of 3D Craniofacial Dysmorphology: Elaborating the Facial Phenotype of Neurodevelopmental Disorders Through the “Prism” of Schizophrenia - Waddington, John L.; Katina, Stanislav; O’Tuathaigh, Colm M. P.; Bowman, Adrian W. (Current behavioral neuroscience reports, 2017)
Purpose of Review In the context of human developmental conditions, we review the conceptualisation of schizophrenia as a neurodevelopmental disorder, the status of craniofacial dysmorphology as a clinically accessible index of brain dysmorphogenesis, the ability of genetically modified mouse models of craniofacial dysmorphology to inform on the underlying dysmorphogenic process and how geometric morphometric techniques in mutant mice can extend quantitative analysis. Recent Findings Mutant mice with disruption of neuregulin-1, a gene associated meta-analytically with risk for schizophrenia, constitute proof-of-concept studies of murine facial dysmorphology in a manner analogous to clinical studies in schizophrenia. Geometric morphometric techniques informed on the topography of facial dysmorphology and identified asymmetry therein. Summary Targeted disruption in mice of genes involved in individual components of developmental processes and analysis of resultant facial dysmorphology using geometric morphometrics can inform on mechanisms of dysmorphogenesis at levels of incisiveness not possible in human subjects.